Arduino IoT Controller for Angle of Attack Measurement with Force Balance - Pratama, Riza Arif; Ikhsan, Muhammad; Permana, Indra (International Journal Software Engineering and Computer Science (IJSECS), 2024)
The force balance system uses the whitestone bridge concept to read the airfoil aerodynamic lift and drag forces while also having a function to control the airfoil angle of attack. It is designed for low subsonic wind tunnels, especially for educational purposes. The system uses Arduino as the microcontroller to read the force data from the load cell sensors and gives commands to the rotary motor stepper to change the airfoil angle of attack. Arduino is combined with a novel mechanical linkage system designed and studied to ensure the sensors can read the correct airfoil lift and drag forces. The angle of attack is controlled with a smartphone to decide the degree of airfoil. The reading of the system is validated using spring balance that pulls the system with magnitudes of 1,1.5, 2, 2.5, and 3 kg in some pulling force angle. The results show that the reading of the system is accurate compared to the theoretical results, with an average error of 2 %. The force measuring tool on the airfoil is the first step in a series of steps to produce the final project, namely the wind turbine. Research suggests that the load cell must be positioned correctly so that the sensor reading error can be increased again. The stepper motor must be turned off the bottom shaft to prevent the airfoil from rotating.